Partisipasi Masyarakat Lokal Dalam Pengelolaan Wisata Bahari Di Pantai Semawang Kelurahan Sanur Kelod - Oktaviani, Putu Devi; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 6 No 2 (2018): VOL 6, NO 2 (2018): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i02.p22, 2019)
Tourism development in Denpasar, especially maritime tourism at Semawang Beach in Sanur Kelod has encourage the local community to participate in developing tourism on Semawang Beach. This phenomenon has create participation of local communities in the management of maritime tourism. This research aim to examine participation of local communities in the management of maritime tourism at Semawang Beach in Sanur Kelod. The advantage that are expected to be achieved from this research are academic and practical advantages. This research is located at Semawang Beach in Sanur Kelod. The limits on the scope of this research includes motivation of local communities in management of maritime tourism and participation of local communities in the management of maritime tourism. Type of research data is in the form of qualitative and quantitative. Source of data obtained from primary and secondary data. Collection data techniques using observation, in-depth interview and documentation. Snowball sampling method has been used to determine informant and respondent The result of this research shows that motivation of local communities in the management of maritime tourism at Semawang Beach in Sanur Kelod is motivation to improve the welfare of the society and the mutual relationship between the maritime tourism with the local citizen. The type of local communities participation in the management of maritime tourism at Semawang Beach in Sanur Kelod are divide by three domains, such as : (1) economic participation, by the local communities work in the field of marine tourism, (2) environtment participation, by implementing thebeach clean program at Semawang Beach, coral reef cleanup program, village deliberations are held to discuss various issues in the environment, participation of local communities in the efforts to protect the environment around Semawang Beach, participation of local communities in lending of vacant land as parking lots, (3) social culture participation, laying of typical Balinese statues and introduce the melukat culture to the tourist. Keywords: Participation, local communities, sustainable tourism, maritime tourism, Semawang Beach